Nutritional and Biological Evaluation of Leaves of Mangifera indica from Mauritius - S. Jhaumeer Laulloo; M. G. Bhowon; S. Soyfoo; L. S. Chua (Journal of Chemistry)
Mango trees are evergreen plants that are present all around Mauritius. In this study, mango leaves, Mangifera indica grown in Mauritius were investigated for their nutritional values involving proximate composition, total flavonoid (TFC), total phenolic (TPC), and mineral content, and phytochemicals as well as its antioxidant and antibacterial properties. The ash, crude fat, neutral detergent fiber (NDF), acid detergent fiber (ADF), and acid detergent lignin (ADL) of the mango leaves were found to be 12.61, 3.92, 35.32, 34.98, and 12.86%, respectively. The calcium content (2.15%) was above the normal required range, while the phosphorus content (0.12%) and crude protein content (13.60%) were within the normal required range of common fodders. The phytochemical results showed the presence of saponins, alkaloids, phenols, tannins, and flavonoids in the crude, EtOAC, and MeOH extracts. The values of TPC and TFC were higher for the EtOAC extract compared to the MeOH extract. Several secondary metabolites were identified from the leaves of the Mangifera indica which include 11 phenols, 4 xanthones, 9 flavanols, 10 benzophenones, 7 terpenoids, and 4 derivatives of gallotannins using UPLC-MS/MS. The presence of these metabolites is responsible for good antioxidant and antibacterial properties. Hence, mango leaves can be exploited for its potential use as a supplementary fodder for ruminants.